Antenatal education for childbirth–epidural analgesia. (September 2018) - Cutajar, Lisa; Cyna, Allan M.
Abstract: The language structures used by antenatal educators have not been previously researched in the context of antenatal childbirth classes. Epidural analgesia for labour is a common, and a frequently asked about, component of antenatal education for parents in hospitals providing maternity care. Aim of the study: We aimed to identify the way information is described and presented by childbirth educators to assess content and determine which language structures such as metaphor, suggestion, information and storytelling are utilized. Design: This observational study of antenatal education was conducted at a single tertiary referral center for maternity care in Western Sydney, Australia. All three childbirth educators agreed to be video recorded whilst providing information to parents during antenatal classes. Audio data was subsequently transcribed and then analysed by two researchers, independently categorising the various language structures and types of information provided. For the purposes of the current study, data concerning a single topic was used for the analysis–'epidural analgesia for labour'. Findings: Language structures used were highly variable between educators, as was the content and time taken for the information being provided. Conclusion and recommendations: Our findings represent a first attempt to identify baseline information used in the clinical setting of antenatal education in order to categories communication structures used. This study has identified areas for further improvements and consistency in the way educators provide information to parents and has important implications for future midwifery practice, education and research.